Flower morphometry of members of the genus Dactylorhiza Necker ex Nevski (Orchidaceae) from the Altai Mountains of Kazakhstan - Aidar Sumbembayev; SAULE ABUGALIEVA; ALEVTINA DANILOVA; EKATERINA MATVEYEVA; DARIUSZ SZLACHETKO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sumbembayev AA, Abugalieva SI, Danilova AN, Matveyeva EV, Szlachetko DL. 2021. Flower morphometry of members of the genus Dactylorhiza Necker ex Nevski (Orchidaceae) from the Altai mountains of Kazakhstan. Biodiversitas 22: 3545-3555. Several species of Dactylorhiza (Orchidaceae) from the Altai mountains of Kazakhstan have been investigated regarding their morphological flower variability. Significant metric characters were identified allowing to differentiate between the four species: D. incarnata, D. fuchsii, D. maculata and D. salina. The morphometric structure of flowers was analyzed by comparing 17 metric parameters in representatives of 11 populations. We identified the most variable and stable traits as well as distinctive features for each species. A high degree of flower morphometric diversity was revealed from principal component analysis for species and populations. Cluster analysis demonstrated the structure of the population diversity. Structural schemes have been compiled from data of the photographic processing of flower morphometry, the analysis of variance ANOVA, and the degree of variation at the population level. Useful characters are provided for further taxonomic work on members of the genus Dactylorhiza in Kazakhstan.